Construction of 1T@2H MoS2 heterostructures in situ from natural molybdenite with enhanced electrochemical performance for lithium-ion batteries. Issue 53 (13th October 2021) - Peng, ChengLong; Shi, Mingming; Li, Fei; Wang, Yang; Liu, Xueqin; Liu, HuaSheng; Li, Zhen
Abstract : Natural molybdenite, an inexpensive and naturally abundant material, can be directly used as an anode material for lithium-ion batteries. Abstract : Natural molybdenite, an inexpensive and naturally abundant material, can be directly used as an anode material for lithium-ion batteries. However, how to release the intrinsic capacity of natural molybdenite to achieve high rate performance and high capacity is still a challenge. Herein, we introduce an innovative, effective, and one-step approach to preparing a type of heterostructure material containing 1T@2H MoS2 crafted from insertion and expansion of natural molybdenite. The metallic 1T phase formed in situ can significantly improve the electronic conductivity of MoS2 . At the same time, 1T@2H MoS2 heterostructures can provide an internal electric field (E-field) to accelerate the migration rate of electrons and ions, promote the charge transfer behaviour, and ensure the reaction reversibility and lithium storage kinetics. Such worm-like 1T@2H MoS2 heterostructures also have a large specific surface area and a large number of defects, which will help shorten the lithium-ion transmission distance and provide more ion transmission channels. As a result, it exhibits a discharge capacity of 788 mA h g −1 remarkably at 100 mA g −1 after 485 cycles and stable cycling performance. It also shows excellent magnification performance of 727 mA h g −1 at 1 A g −1, compared to molybdenite concentrate. Briefly, this work's heterostructure architectures open up a new avenue for applying natural molybdenite in lithium-ion batteries, which has the potential to achieve large-scale commercial applications.